Biochemical and Genetic Analysis Identify CSLD3 as a beta-1, 4-Glucan Synthase That Functions during Plant Cell Wall Synthesis. Issue 5 (13th March 2020) - Yang, Jiyuan; Bak, Gwangbae; Burgin, Tucker; Barnes, William J.; Mayes, Heather B.; Peña, Maria J.; Urbanowicz, Breeanna R.; Nielsen, Erik
Abstract : A combination of genetic rescue and biochemical reconstitution experiments demonstrate that the Arabidopsis ( Arabidopsis thaliana ) CSLD3 cell wall synthase is a beta-1, 4-glucan synthase. Abstract: In plants, changes in cell size and shape during development fundamentally depend on the ability to synthesize and modify cell wall polysaccharides. The main classes of cell wall polysaccharides produced by terrestrial plants are cellulose, hemicelluloses, and pectins. Members of the cellulose synthase (CESA) and cellulose synthase-like (CSL) families encode glycosyltransferases that synthesize the β-1, 4-linked glycan backbones of cellulose and most hemicellulosic polysaccharides that comprise plant cell walls. Cellulose microfibrils are the major load-bearing component in plant cell walls and are assembled from individual β-1, 4-glucan polymers synthesized by CESA proteins that are organized into multimeric complexes called CESA complexes, in the plant plasma membrane. During distinct modes of polarized cell wall deposition, such as in the tip growth that occurs during the formation of root hairs and pollen tubes or de novo formation of cell plates during plant cytokinesis, newly synthesized cell wall polysaccharides are deposited in a restricted region of the cell. These processes require the activity of members of the CESA-like D subfamily. However, while these CSLD polysaccharide synthases are essential, the nature of the polysaccharides they synthesize has remained elusive. Here, we use a combination of genetic rescue experiments with CSLD-CESA chimeric proteins, in vitro biochemical reconstitution, and supporting computational modeling and simulation, to demonstrate that Arabidopsis ( Arabidopsis thaliana ) CSLD3 is a UDP-glucose-dependent β-1, 4-glucan synthase that forms protein complexes displaying similar ultrastructural features to those formed by CESA6.